If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 17 = 15x + -111 Reorder the terms: 17 + 6x = 15x + -111 Reorder the terms: 17 + 6x = -111 + 15x Solving 17 + 6x = -111 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 17 + 6x + -15x = -111 + 15x + -15x Combine like terms: 6x + -15x = -9x 17 + -9x = -111 + 15x + -15x Combine like terms: 15x + -15x = 0 17 + -9x = -111 + 0 17 + -9x = -111 Add '-17' to each side of the equation. 17 + -17 + -9x = -111 + -17 Combine like terms: 17 + -17 = 0 0 + -9x = -111 + -17 -9x = -111 + -17 Combine like terms: -111 + -17 = -128 -9x = -128 Divide each side by '-9'. x = 14.22222222 Simplifying x = 14.22222222
| 2x+8=4(x-3) | | 2v+6=-4(1v+3) | | 4z=-40 | | x+35=84-74 | | 180-x=2(x+20) | | 180x=2(x+20) | | -5.7p+10.16=-65.08 | | x+20=180-2(x+20) | | 2[x+3]=-4[x+1] | | -3b+ax=x-4 | | x+20=180-(x+20) | | 147-3b^2=0 | | (2b^5-5b^4+8b^3-12b^2+12b-9)= | | 15y-16=7y-15 | | 0.2n+3= | | 3(2x+5)=5x+12 | | 7[3-(-4x-1)]=252x+84 | | 10x-8=102 | | 8x-2(x-5)=x+5 | | 31s+10=-14s | | V^2+12v-24=0 | | 6(2t+5)=4 | | -45=-6(-36-4) | | 7n^2-52n-32=0 | | x^2-x=552 | | 20+x=2(20+x) | | (3p-4)=35 | | 2(x-5)+3(2x-8)= | | 16=8 | | 6x+24=4.7 | | 9x^2-5x= | | 16=0.5r |